La hibridez comunicativa en imaginarios latinoamericanos en la cultura digital - Pacheco Díaz, Angélica (2024)
This article addresses the hybridity of communication to create interdisciplinary narratives of the common and public imaginaries of Latin American women, through an intercultural plot from their biographical space.Based on an Ibero-American investigation that culminated in a publication of transmedia experience and that is in the dissemination stage in various local, national and international spaces, this article presents an analysis of this intercultural narrative and its cultural hybridization in common imaginaries.A methodology will be applied based on qualitative analyzes of the contents of intercultural communication of the project based on a circular narrative model of the plot designed for the construction of narratives with women from Latin America.